Teacher Performance : Principal Supervision, Work Climate, And Ability - Anggie Yulpa Aqtania; Septa Diana Nabella; Amirullah, Amirullah; Sabri, Sabri; Rahman Syahputra (International Journal of Economics, Business and Innovation Research, 2024)
The purpose of this study is to analyze and test whether there is an influence between principal supervision, work climate, and pedagogic ability on the performance of Non-Formal Early Childhood teachers in Sagulung District in 2014. The population of this study is all Non-Formal Early Childhood educators in Sagulung District.The research data was analyzed using Path Analysis, with the dependent variable being teacher performance and the independent variable being principal supervision, work climate, and pedagogical ability. The results showed that the supervision of the principal did not have a significant effect on the performance of early childhood teachers with a direct influence of 3.0%. The work climate has a significant effect on teacher performance with a direct influence of 65.9%. Pedagogic ability did not have a significant effect on teacher performance with a direct influence of 1.0%. However, the principal's supervision, work climate, and pedagogic ability together significantly affected teacher performance with a direct influence of 71.4% and the rest were influenced by other variables that were not studied in this study (28.4%).